PENGUKURAN MODULUS YOUNG SENAR PANCING DENGAN METODE ANALISIS FREKUENSI DAWAI - Nidar Karyati Gulo; Albertus Hariwangsa Panuluh (Jurnal Kumparan Fisika)
The research has been conducted to determine the Young Modulus value of the fishing line with frequency analysis on a string by using a sound sensor. The fishing line made of Nylon Monofilament and Stainless Steel Nylon Coat. The diameter of the fishing line with each material consisted of 0.25 mm. The fishing line vibration events ware displayed on the graph of the relationship between pressure and time in the Logger pro program. The graph of the relationship between pressure and time was then transformed into an FFT graph of the amplitude relationship to frequency. Then the frequency value which was obtained from the FFT was used to determine the wave velocity value of the fishing line. The average wave velocity value was obtained by graphing the frequency relation to one of each string length. After obtained the average wave velocity value of the fishing line the Modulus Young value can be determined by the equation of the square wave velocity relationship times the mass per length times the cross-sectional area. In this study, the Young Modulus value of Nylon Monofilament fishing line was (1.94±0.09) GPa and the Young Modulus value of the Stainless Steel Nylon Coat fishing line was (45.05±2.05) GPa.